2022
DOI: 10.1103/physrevb.106.155140
|View full text |Cite
|
Sign up to set email alerts
|

Finding spectral gaps in quasicrystals

Abstract: We show how the spectrum of normal discrete short-range infinite-volume operators can be approximated with two-sided error control using only data from finite-sized local patches. As a corollary, we prove the computability of the spectrum of such infinite-volume operators with the additional property of finite local complexity and provide an explicit algorithm. Such operators appear in many applications, e.g. as discretizations of differential operators on unbounded domains or as so-called tight-binding Hamilt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 114 publications
(144 reference statements)
0
3
0
Order By: Relevance
“…Recently, it was shown that spectral gaps exist in Hamiltonian with quasicrystalline order. [63] Quasicrystal considerations in Holography, the basic structure of nature, and cosmology are discussed in ref. [64][65][66][67][68][69][70][71].…”
Section: Space-time Quanta and Spectral Mass Gapmentioning
confidence: 99%
“…Recently, it was shown that spectral gaps exist in Hamiltonian with quasicrystalline order. [63] Quasicrystal considerations in Holography, the basic structure of nature, and cosmology are discussed in ref. [64][65][66][67][68][69][70][71].…”
Section: Space-time Quanta and Spectral Mass Gapmentioning
confidence: 99%
“…Characterizing the spectra of quasi-periodic differential operators is a longstanding and fascinating problem [2,3]. In particular, one-dimensional Schrödinger operators with quasi-periodic potentials have been widely studied.…”
Section: Introductionmentioning
confidence: 99%
“…Gapless edge modes are also expected to be relevant there. So far, they have been studied only in the single-particle setting with the goal to numerically distinguish the behavior of edge modes from bulk spectrum [39] or to prove the existence of a bulk gap in the presence of gapless edge modes [28]. These approaches have yet to be generalized to the many-body setting.…”
Section: Introductionmentioning
confidence: 99%